Thinning of the temporal and insular cortex is associated with negative symptoms and impaired attention in Chinese chronic schizophrenia patients with deficit syndrome - Jin Li; Xiaobin Zhang; Junjie Wang; Haidong Yang; Man Yang; Ju Gao; Xiangdong Du (BMC Psychiatry)
Abstract Background The considerable clinical heterogeneity of schizophrenia poses significant challenges for elucidating its neurobiology. The concept of deficit schizophrenia (DS) is a valuable framework for addressing the heterogeneity of schizophrenia. Growing evidence suggests notable differences between deficit (DS) and nondeficit (NDS) schizophrenia, indicating that DS could represent a separate disease entity. Methods We aimed to use FreeSurfer to identify specific changes in cortical thickness among NDS patients and healthy controls (HCs) in a Chinese sample. Furthermore, we examined the potential relationships between changes in cerebral cortical thickness and negative symptoms and attention deficits in DS patients. A total of 142 subjects (48 HCs, 50 NDSs, and 44 DSs) underwent MRI scans and completed the assessment of psychopathological severity and cognitive performance. Results Compared with HCs, DS and NDS patients presented common cortical thinning in the right insula, whereas cortical thinning in the left supramarginal cortex was more prominent in DS patients. We also found that thinning of the temporal and insular cortex was correlated with negative symptoms and impaired attention in DS patients. Conclusions Cortical thinning in specific brain regions in DS patients was found to be correlated with specific clinical and cognitive symptoms.